Ecological and sexual roles of scale mechanoreceptors in two species of Neotropical freshwater snake (Dipsadinae: Helicops). (25th September 2021) - García-Cobos, Daniela; Gómez-Sánchez, Diego A; Crowe-Riddell, Jenna M; Sanders, Kate L; Molina, Jorge
Abstract: Understanding the roles of ecological and sexual selection in the variation of sensory systems may elucidate aspects of the natural history of organisms. Little is known about the evolution of mechanoreception in snakes and how the function and structure of mechanoreceptors vary between species or sexes. Here, we describe the internal and external morphology of cephalic mechanoreceptor sensilla and quantify inter- and intraspecific variation in four sensilla traits of two freshwater snake species that differ in their habitat and diet preferences, Helicops pastazae and Helicops angulatus, by combining scanning electron microscopy (SEM), histological techniques and image analyses. SEM showed sensilla as prominent evaginations of the epidermis surrounded by concentric rings, with H. pastazae having larger and more heterogeneous sensilla. In both species, histology showed a reduction in the outer epidermal layer above the sensilla with a grouping of dermally derived central cells below it. Higher values of sensilla traits were found in H. pastazae, except for the chin-shields. We also found that males of both species had significantly higher values of sensilla traits on all of the scales examined. We hypothesize that the variation in both qualitative and quantitative traits in scale sensilla might be a consequence of differences in foraging and/or reproductive strategies between species and sexes.